2022
DOI: 10.7554/elife.56726
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila TRPγ is required in neuroendocrine cells for post-ingestive food selection

Abstract: The mechanism through which the brain senses the metabolic state, enabling an animal to regulate food consumption, and discriminate between nutritional and non-nutritional foods is a fundamental question. Flies choose the sweeter non-nutritive sugar, L-glucose, over the nutritive D-glucose if they are not starved. However, under starvation conditions, they switch their preference to D-glucose, and this occurs independent of peripheral taste neurons. Here, we found that eliminating the TRPγ channel impairs the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Compared to the controls, the Dh44 - GAL4 / UAS - Kir2.1 flies exhibited lower carbohydrate levels and increased lipid levels. We previously proposed that TRPγ holds DH44 neurons in a state of afterdepolarization, thus reducing firing rates by inactivating voltage-gated Na + channels 11 . At the physiological level, this induces the consistent release of DH44 and depletion of DH44 stores, resulting in nutrient utilization and storage malfunctions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the controls, the Dh44 - GAL4 / UAS - Kir2.1 flies exhibited lower carbohydrate levels and increased lipid levels. We previously proposed that TRPγ holds DH44 neurons in a state of afterdepolarization, thus reducing firing rates by inactivating voltage-gated Na + channels 11 . At the physiological level, this induces the consistent release of DH44 and depletion of DH44 stores, resulting in nutrient utilization and storage malfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…The starvation sensitive phenotype in the trp mutants may have been due to decreased carbohydrate storage in tissues, including glucose, trehalose, and glycogen. However, we previously demonstrated that trp mutants could utilize carbohydrates under starved conditions 11 . Furthermore, the elevated whole-body TAG levels in the trp mutant flies might suggest that they were unable to break down stored lipids even under starving conditions.…”
Section: Trp Mutants Exhibit Starvation Susceptibility and Deficits ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results identify the neuropeptide DH44 as a key regulator, in addition to a classical neurotransmitter ACh, in pC1 and possibly other dsx neurons for the sexually dimorphic behavioral prioritization. DH44 has long been thought to be predominantly expressed only in six cells in the pars intercerebralis (PI) region, which is regarded as a neuroendocrine center regulating various physiological processes and behaviors such as fluid secretion[35], stress tolerance[49, 50], rest: activity rhythms[36, 51, 52], brain nutrient sensing[37, 5355] and female sperm ejection[38]. We find that DH44 also functions in the central pC1 neurons to modulate locomotor, sexual and feeding behaviors in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae were reared from eggs on a standard medium containing 1 mM ATR (R2500, Sigma-Aldrich). Third-instar wandering larvae were pinned down on a silicon dish (Silpot 184, Dow Corning Toray) and were dissected along the dorsal midline in either calcium-free HL3.1 buffer 81 (70 mM NaCl, 5 mM KCl, 4 mM MgCl 2 , 10 mM NaHCO 3 , 5 mM trehalose, 115 mM sucrose, 5 mM HEPES, pH 7.2), sugar-free buffer 82 (108 mM NaCl, 5 mM KCl, 8.2 mM MgCl 2 , 4 mM NaHCO 3 , 1 mM NaH 2 PO 4 , 5 mM HEPES, pH 7.5), or sugar-free buffer with GABA (γ-Aminobutyric acid, A2129, Sigma-Aldrich). Note that using the “calcium-free” buffer was key to avoid brain movements due to larval muscle contractions.…”
Section: Methodsmentioning
confidence: 99%